The Effect Of Green Coconut Water On The Levels Of Dysmenorrhea Pain Among Adolescent Girls In Berekah Village Sukabumi Regency In 2021 - Triana Indrayani; Siti Hasanah Fikria; Sri Dinengsih (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aimed to determine the effect of giving green coconut water on dysmenorrhea pain among adolescent girls in Berekah village, Sukabumi district in 2021. This study was a Quasi Experiment using a pretest-posttest design with a control group. The data were analyzed using the Paired T-Test to determine the difference in scores in one group and the Independent T-Test to determine the difference in scores between groups. The results showed that there was a significant difference in the dysmenorrhea pain scale before and after being given green coconut water (p <0.05).Conclusion: Green coconut water has an effect on reducing the dysmenorrhea pain scale among adolescent girls in the village of Berekah, Sukabumi district. It is hoped that green coconut water can be applied thoroughly as a traditional treatment in dealing with dysmenorrhea pain in adolescent girls.Keywords: adolescent girls, dysmenorrhea, green coconut water